The geopolitics of knowledge and the coloniality of power. Interview with Walter Mignolo (Polis (Santiago), 2018)
The interview covers such concepts as "geopolitics of knowledge" as applied to Latin America and argues that the region is a geopolitical product manufactured and imposed by "modernity", where "Latin America" was manufactured as something displaced from modernity; or from philosophy, which is narrated from Greece to Europe, leaving the rest of the planet outside the history of philosophy. The respondent invites to stop thinking that what counts as knowledge is written in some languages and comes from certain places. From this approach, he refers to topics such as the reciprocal infection and interaction between indigenous and Marxist cosmology, the  distinction between "interculturalism" and "multiculturalism", and the re-articulation of power in "World War IV."
Keywords: geopolitics of knowledge; Latin America; modernity; history of philosophy